Local Election Integrity in the Digital Era and the Role of Witnesses Election Participants in Regional and Legislative Elections - Saipul Saipul; Yunizir Yunizir; Merita Auli; Khairunnisa Khairunnisa (Journal of Creative Power and Ambition (JCPA), 2026)
General elections are the primary instrument for realizing popular sovereignty and constitutional democracy in Indonesia. Elections, both regional head elections (Pilkada) and legislative elections (Pileg), require integrity assurance to ensure that the election results truly reflect the will of the people. This study aims to analyze the role of digital literacy and reporting-based election participant witnesses in maintaining the integrity of the results of the regional head elections (Pilkada) and legislative elections (Pileg) at the local level, as well as to examine the effectiveness of digital technology integration in increasing election transparency and accountability. The results show that 82% of respondents believe digital technology improves the effectiveness of election supervision, 79% stated that the digital reporting system increases the transparency of election results, and 74% believe that digital documentation can reduce the potential for data manipulation at the polling station (TPS) level. The level of digital literacy of witnesses is in the moderate to high category, with 41% of respondents having high digital skills. The use of digital technology also speeds up the process of reporting violations by up to 45% compared to manual methods. However, the implementation of digital-based election supervision still faces various challenges, including the spread of political disinformation and hoaxes found by 63% of respondents, limited digital information verification capabilities (58%), and internet infrastructure constraints in several rural areas (29%).